Mannitol vs. methacholine in the evaluation of airway responsiveness in bakers’ asthma - Ewa Nowakowska-Świrta (International Journal of Occupational Medicine and Environmental Health, 2020)
Objectives Various indirect or direct airway challenge tests are used to measure nonspecific bronchial hyper-responsiveness (NSBHR). The evaluation of NSBHR in diagnosing occupational asthma (OA) is performed, e.g., to monitor the specific inhalation challenge test (SICT). The aim of this study was to preliminarily compare the results of methacholine and mannitol inhalation challenge tests in SICT monitoring in bakers with work-related airway symptoms.